Inhibition of order–disorder phase transition and improvements in the BICUVOX.1 properties by using yttria-stabilized zirconia particles. Issue 1 (January 2015) - Piva, R.H.; Piva, D.H.; Venturini, J.; Floriano, R.; Morelli, M.R.
Abstract: Composite solid electrolytes were prepared varying the addition of yttria-stabilized zirconia (3Y-TZP) from 3 to 26 wt% using a matrix of copper-substituted bismuth vanadate (BICUVOX.1). The effects of stabilized zirconia concentration were added and their relation with the tensile strength, thermal expansion, phase transition and electrical conductivity were evaluated. When compared to pristine BICUVOX.1, the addition of 26 wt% of 3Y-TZP led to an increase of 144% in tensile strength and a reduction of the thermal expansion coefficient from 12.3×10 −6  °C −1 to 9.6×10 −6  °C −1 . Such improvements stems from grain growth inhibition due to the Zener pinning effect. Impedance measurements and thermal analyses showed that the addition of high zirconia concentrations is an effective way to prevent the γ′↔γ phase transition in the BICUVOX.1 matrix. Nevertheless, the total electrical conductivity has been continuously reduced with a progressive increase in the amount of zirconia.